Anti-Xa effect of a low molecular weight heparin (dalteparin) does not accumulate in extended duration therapy for venous thromboembolism in cancer patients - Kovacs, Michael J.; Levine, Mark N.; Keeney, Michael; MacKinnon, Karen M.; Lee, Agnes Y. (Thrombosis and Haemostasis, 2005)
Many patients with venous thromboembolism are being treated with low molecular weight heparin for extended periods of time. It is not certain if it is necessary to assess anti-Xa levels for extended treatment periods. This study is a prospective assessment of anti-Xa levels in patients on long-term therapy for acute venous thromboembolism who have active cancer. Consecutive consenting patients from one center in a multicenter trial that compared 6 months of low molecular weight heparin with oral anticoagulant therapy were treated with therapeutic doses of dalteparin (200 IU per kilogram) subcutaneously daily. Anti-Xa levels were assessed at the end of weeks 1 and 4, 4–6 hours after injection of dalteparin. Patients were followed for bleeding and recurrent venous thromboembolism. There were 24 patients who had anti-Xa levels measured at weeks 1 and 4. Two other patients had week 1 measurements performed but died before the week 4 sample was collected due to their underlying cancer. The mean anti-Xa levels at weeks 1 and 4 were 1.11 and 1.03 anti-Xa units/ml respectively (P=0.13). These results suggest that for patients with active cancer receiving extended duration therapy with low molecular weight heparin (dalteparin) there is no accumulation of anti-Xa effect over the first month of therapy. Monitoring of anti-Xa levels in this situation is usually not required.
Keywords: Low molecular weight heparin; anti-Xa levels; VTE; cancer